Praying twice extolling prayer through sung psalms - Velasco, Benedic Justine Usman
The main concept of this project is to put into music certain verses of the bible. This concept is timely because, for a country with deep love for choral and vocal music, nowadays there is silence in the composition of new and original church music. Through this new music compositions, catholic church music will be revitalized and the values that the bible aims to spread will be strengthened and magnified. The words of the bible are powerful enough on their own. The main importance of music in Mass is to bring participation from the people.